2016
DOI: 10.1021/acs.jctc.5b01193
|View full text |Cite
|
Sign up to set email alerts
|

Gauging the Performance of Density Functionals for Lanthanide-Containing Molecules

Abstract: Several density functional approaches have been considered for their ability to predict enthalpies of formation and bond dissociation energies for lanthanide-containing molecules. To enable comparison with experiment, the Ln54 set, introduced here, is compiled to include lanthanides both in the common 3+ oxidation state as well as in more exotic oxidation states. Due to the magnitude of the experimental uncertainties a "lanthanide chemical accuracy" of 5.0 kcal mol(-1) is proposed. The density functionals cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 62 publications
1
60
1
Order By: Relevance
“…A detailed assessment of approximate density functionals is crucial for drawing meaningful conclusions from quantum chemical studies of transitionmetal complexes and their reactions. [1][2][3][4][5][6][7][8][9][10][11] One of the few benchmark sets for large transition-metal complexes containing experimental gas-phase reference data is our WCCR10 reference set of ligand bonding energies. 12 The WCCR10 set comprises ten experimentally measured gas-phase ligand dissociation energies obtained from threshold collision-induced decay (T-CID) experiments.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed assessment of approximate density functionals is crucial for drawing meaningful conclusions from quantum chemical studies of transitionmetal complexes and their reactions. [1][2][3][4][5][6][7][8][9][10][11] One of the few benchmark sets for large transition-metal complexes containing experimental gas-phase reference data is our WCCR10 reference set of ligand bonding energies. 12 The WCCR10 set comprises ten experimentally measured gas-phase ligand dissociation energies obtained from threshold collision-induced decay (T-CID) experiments.…”
Section: Introductionmentioning
confidence: 99%
“…At higher HF‐exchange percentage, that is, donation in the 5d orbitals, the spin‐contamination is low, inducing a better energetic evaluation. However, this behavior is not general and, in cases where ligands are not involved in high charge transfer (for example trihalide lanthanide complexes), the energies are better evaluated by using lower HF exchange, with donation in the 4f orbitals.…”
Section: Resultsmentioning
confidence: 99%
“…reported an energy comparison between two density functionals, B3PW91 and B3LYP, and the MP2 method, using small core relativistic effective core potentials (RECP), and they chose B3PW91 for further chemical studies . Recently, the performance of several density functionals over energies of diatomic lanthanide molecules was evaluated by Grimmel et al . They showed that TPSS was one of the best density functionals, and that less accurate results were obtained when more Hartree–Fock exchange was included in the functional.…”
Section: Introductionmentioning
confidence: 99%
“…Grimmel et al benchmarked a number of DFT functionals that range from LDA to double hybrid ones for predicting properties of Ln-containing molecules. 329 54 experimental HOFs of Ln species were employed as the reference data set. They proposed that 5.0 kcal/mol represented the “lanthanide chemical accuracy” based on the uncertainty of the experimental values.…”
Section: Modeling Transition Metal-containing Species Using Quantum Mmentioning
confidence: 99%